(untitled) (Comprehensive Journal of Science, 2026)
The repair process of industrial piping systems is a serious problem because of its inaccessibility, unsafe conditions, and high cost of operations. The manual inspection and maintenance techniques used in the traditional processes tend to expose the workers to risks of safety and also they consume more time. This paper suggests developing a basic, inexpensive, robotic system that would be utilized specifically to examine and inspect the piping system within industrial facilities as well as carry out its simple maintenance. The suggested robotic system is aimed at mechanical simplicity, modularity, and deployment simplicity at a cost of a reasonable level of functionality and reliability. The robot can follow both straight and curved pipes, identify any surface deformities (corrosion and blockages) and provide real time visual information. The design process combines actuator selection, control architecture and mechanical modeling with components that are readily available. The proposed mechanism is experimentally validated to behave in simulated industrial conditions with a high level of accuracy. The results indicate that compared to the use of complex and expensive inspection robots, simple robots can be used to provide an effective alternative to robots to perform simple robotic tasks, especially to small and medium-sized industrial facilities. The study has a contribution to the research of industrial robotics by highlighting matters of practical design and low-cost automation of infrastructure repairs.